Pengembangan Modul Pembelajaran Aljabar Linear menggunakan Software Matrix Laboratory (Matlab) di Prodi Tadris Matematika - Desty Septianawati; Zulkarnain; Khairiyah; Sarika Putri (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
This research aims to produce a Linear Algebra learning module with MATLAB Software in the Tadris Mathematics Study Program that can be used practically and effectively. This research is development research based on the stages of Dick & Carey. The stages of research carried out in the development of this module are: Needs Analysis, Instructional Analysis, Context Analysis (students and content), The stage of writing performance objectives, Developing assessment instruments, Choosing learning strategies, Developing teaching materials, Designing and conducting formative evaluations, Revising, and The stage of designing and conducting a summative evaluation. The result of the research is that there are significant differences in learning outcomes in the pretest and posttest scores, which means an increase in test scores after using the linear algebra learning module with MATLAB software.